PENDIDIKAN MULTIKULTURAL: KONSEPSIDAN IMPLEMENTASINYA DALAM PEMBELAJARAN - Zubaedi Zubaedi (Jurnal Cakrawala Pendidikan, 2008)
The multiculturaleducation concept is analtemative solution to reducingracial antagonisms in our·country. Multicultural education is·education thatvalues cultural pluralism or an education model that aims to promote thetransformation ofthe educational process to reflect the ideals of democracy inapluralistic society and structural· equality within a larger society. This. conceptaffirms that schools should be oriented toward the cultural enrichment of. allchildrenand recognize cultural diversity as· reality in. Indonesia that should.bepreserved and extended. Thus, one of its important goals is to help all studentsto acquire knowledge, attitudes, and skills needed to .function effectively ina pluralistic democratic society and to interact, negotiate, and comtnunicatewithpeople from diverse groups in order to create a civic and moral community thatworks for the common good. There are three essential goals ofmulticulhrraleducat;ion.The first is to enhance sensitivity to and understanding of others, including cultural groupsin Indonesia and other nations. The second is.· toenhancethe ability to make decisions and take effective actions .based.onamulticultural analysis and synthesis. The third is to enhance understanding oftheprocess.ofstereotypmg, a low degree of stereotypical.thinking, and pride inselfand· respect for other people